"Dere's Not Just One Kind of Fat": Embodying the "Skinny"- Self Through Constructions of the Fat Masculine Other. (October 2013) - Norman, Moss E.
In the current sociopolitical context, the lean, muscular body has come to epitomize masculine health and beauty. Not all boys and young men, however, unequivocally subscribe to dominant constructions that position fatness as unhealthy and unattractive. Using qualitative inquiry with thirty-two "skinny" or "normal"-bodied young men (thirteen to fifteen years of age), I demonstrate that fat talk is a prominent resource through which "normal" masculine embodiment is achieved. More specifically, I reveal that sociocultural positioning influences how young men take up, make sense of, and articulate constructions of fatness and demonstrate how such articulations function in the materialization of their "normal" embodied subjectivities. I also examine how fat masculinities operate differently within diverse emplaced contexts and in relation to distinct discursive communities. Such a line of investigation I argue helps to reveal the ways in which power relations of privilege and oppression are performatively embodied in everyday contexts.